2020
DOI: 10.1371/journal.pone.0234711
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of organizational readiness to implement an electronic health record system in a low-resource settings cancer hospital: A cross-sectional survey

Abstract: Background Organizational readiness for change is a key factor in success or failure of electronic health record (EHR) system implementations. Readiness is a multifaceted and multilevel abstract construct encompassing individual and organizational aspects, which makes it difficult to assess. Available tools for assessing readiness need to be tested in different contexts. Objective To identify and assess relevant variables that determine readiness to implement an EHR in oncology in a low-and-middle income setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 34 publications
(72 reference statements)
2
47
0
1
Order By: Relevance
“…Training has been identified as one of the key success factors in technology acceptance. Commensurate to our findings, receiving necessary training prior to using the system has been encouraged in several other studies [6], [38], [44], [19], [28], [21], [40], [30], [33]. Training equips users with the knowledge of the system [20], gives a chance to acclimate to the new processes and in the long run boosts confidence to use the system.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Training has been identified as one of the key success factors in technology acceptance. Commensurate to our findings, receiving necessary training prior to using the system has been encouraged in several other studies [6], [38], [44], [19], [28], [21], [40], [30], [33]. Training equips users with the knowledge of the system [20], gives a chance to acclimate to the new processes and in the long run boosts confidence to use the system.…”
Section: Discussionsupporting
confidence: 64%
“…Lacking digital skills to operate a system can be aggravated by the little or no formal education. As reported in other studies [20], [24], [37], [40] the lack of ICT skills to operate digital technologies was a very big impediment to adoption. Whereas a study conducted in Finland indicated that digital literacy does not have a direct impact on adoption [58], research conducted in Uganda, found out that expectant mothers did not use digital health technologies in their routine antenatal care practices because they lacked technical skills to operate the internet, computers and smartphones [29].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…For example, an organization has to be willing and capable to implement a program for an effective outcome [6]. Studies indicate that about 50% of programs fail due to poor organisational readiness prior program implementation yet there is a dearth in the literature to indicate organizational readiness to implement the 3HP program among high burden, low-income TB settings such as Zimbabwe [7]. Such a gap in knowledge affects the optimum response to the TB preventive efforts of the country.…”
Section: Introductionmentioning
confidence: 99%